Kinerja Ruas Jalan Urip Sumoharjo Depan Kantor Gubernur Di Era New Normal - Louise Elizabeth Radjawane; Fandy Irwanto Pasenggong; Rais Rachman (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
The Covid-19 pandemic affects the mobility of the people of Makassar City in particular, so the local government has made several policies to reduce the potential for the spread of disease outbreaks, one of which is the new normal so that it can affect the performance of these roads which have high activity. This study aims to determine the performance of urban sections during the new normal period and the Indonesian Road Capacity Manual, 1997 method is used as a reference. Increasing traffic flow decreases the average space velocity and but increases the density value and the degree of saturation, this decreases the segment performance. The lower the average spatial velocity the higher the density value. With the alternative of increasing the performance of the section, it can increase the level of road service to C at the highest flow and speed, reduce the density and degree of saturation.